A4NH 2018 annual report highlights: Flagship 2 - CGIAR Research Program on Agriculture for Nutrition and Health (International Food Policy Research Institute, 2019)
This includes three highlights document for Flagship 2 of the CGIAR Research Program on Agriculture for Nutrition and Health: Highlight 1: Biofortification’s Growing Global Reach Highlight 2: Building the Evidence Base Highlight 3: Engaging Policymakers